Hopping Hotspots: Global shifts in marine biodiversity - Renema, Willem; Bellwood, D.; Braga, J; Bromfield, K; Hall, R; Johnson, K; Lunt, P; Meyer, C; McMonagle, L; Morley, R; O'Dea, A; Todd, J; et al. (The American Association for the Advancement of Science, 2008)
Hotspots of high species diversity are a prominent feature of modern global biodiversity patterns. Fossil and molecular evidence is starting to reveal the history of these hotspots. There have been at least three marine biodiversity hotspots during the past 50 million years. They have moved across almost half the globe, with their timing and locations coinciding with major tectonic events. The birth and death of successive hotspots highlights the link between environmental change and biodiversity patterns. The antiquity of the taxa in the modern Indo-Australian Archipelago hotspot emphasizes the role of pre-Pleistocene events in shaping modern diversity patterns.